The effect of weighted vest use during in-season, small-sided games training on young soccer players` performance - Lagodimos, P.; Thomakos, P.; Methenitis, S.; Paizis, C. (Journal of Sports Sciences, 2024)
The aim of the present study was to investigate the effect of weighted vest on-field small-sided games (SSG) soccer training, during the in-season period, on body composition and soccer-specific performances, in young, trained soccer players. A counterbalance study design was adopted, in which the fourteen well-trained players (age: 19.1 ± 0.5 yrs, body mass: 70.3 ± 5.3 kg, body height: 180.3 ± 3.0 cm, body fat: 9.2 ± 4.1%) performed both the Interventional (Vest) and Control (Con) training routines (6 weeks/season; 5 training sessions/week; 1 match/week), in different occasions (winter/spring period). Con group followed a regular weekly training plan. When the Con group performed their intense training sessions, Vest group performed only the on-field SSGs training wearing a vest (12.5% of athletes` body mass). All the evaluations were performed one week before and after each training period. Statistical analyses include repeated ANOVA and T-test (p < 0.05). Significant increases in sprinting, jumping, change of direction (COD), aerobic and anaerobic performances were observed only after Vest intervention (-4.7 ± 2.2% to 11.2 ± 4.2%; p < 0.05). Significant changes were observed only after Vest training, compared to Cont (p < 0.05). These results suggest that using a weighted vest, during the in-season, onfield SSG training two times/week induces greater increases in young soccer players` sprinting, jumping, COD, aerobic and anaerobic performances.